Usage and appraisal of educational media by homeopathic therapists - A cross sectional survey - Escher Max; Vollmar Horst; Holling Andreas; Raak Christa; Ostermann Thomas (BMC, 2012)
Abstract Background During recent years the market for homeopathic education media has increasingly diversified with old (books, seminars) and new media (video-seminars, pc-programs, homeo-wiki and internet-courses). However, little is known about homeopaths' preferences in using educational media and their requirements of this topic. Aim This survey was designed to gain a better understanding of the usage and appraisal of educational media by homeopaths. Methods 192 homeopathic practitioners (GPs and health practitioners) at a educational conference were asked to answer a standardized questionnaire covering the topics "formal education and context of work" (9 items), "homeopathic practise and usage (24 items), "utilization of educational media" (9 items) and "favoured attributes for educational media" (11 items). Results Out of 192 homeopaths who attended the conference, 118 completed the questionnaire (response rate 61.5%). For their continuing homeopathic education they predominantly indicated to use books (scale value from 0 = never to 2 = always: 1.72) and seminars (1.54) whereas journals (0.98) and the internet (0.65) were used less often. The most favoured attributes concerning medical education media were reliability (1.76), relevance for clinical practice (1.74) and user friendliness (1.6). Less favoured attributes were inexpensiveness (1.1), graphical material (0.92) and interactivity (0.88). Conclusions The survey illustrates the current situation of medical education media in homeopathy. Although there are parallels to earlier research conducted in conventional GPs, homeopaths are more likely to refer to classical media. New education tools should be designed according to these preferences.